CLASSROOM ACTION RESEARCH TRAINING TO IMPROVE THE QUALITY OF PROFESSIONAL TEACHERS - R Siti Pupu Fauziah; Helmia Tasti Adri; Irman Suherman; Syukri Indra; Afridha Sesrita; Didin Syamsudin; Desky Halim Sudjani (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
This research is motivated by the low interest and ability of elementary school teachers in compiling and producing classroom action research to support their professional careers as teachers. The purpose of this study was to increase teachers' understanding of the importance of classroom action research scientific work for professional teachers. The method used in this activity is service with training for teachers in the Bogor Regency, West Java. Community service activities are carried out in Building C, Djuanda University, Bogor. The results of the research show that this community service activity has a good impact on teachers and can increase teachers' understanding of PTK. This service produces 10 articles for teachers as a distribution of activities. The conclusion of this study is that training activities to increase PTK writing skills for teachers can improve teachers' understanding and ability to master and implement CAR and can compose writing in the form of classroom action research